Investigation of the effects of prostaglandin E2 on equine superficial digital flexor tendon fibroblasts in vitro - Cissell, J. M.; Milton, S. C.; Dahlgren, L. A. (Veterinary and Comparative Orthopaedics and Traumatology, 2010)
Objectives: To evaluate the effects of pros-taglandin E2 (PGE2) treatment on the metabolism of equine tendon fibroblasts in vitro to aid in investigating the response of tendon fibroblasts to injury and novel therapeutics.Methods: Superficial digital flexor tendon fibroblasts isolated via collagenase digestion from six young adult horses were grown in monolayer in four concentrations of PGE2 (0, 10, 50, 100 ng/ml) for 48 hours. Cells and medium were harvested for gene expression (collagen types I and III, cartilage oligomeric matrix protein [COMP], decorin, and matrix metalloproteinase-1, –3, and –13), biochemical analysis (glycosaminoglycan, DNA, and collagen content), and cytological staining.Results: Gene expression for collagen type I was significantly increased at 100 ng/ml PGE2 compared to 10 and 50 ng/ml. There were not any significant differences detected for gene expression of collagen type III, COMP or dec-orin or for biochemical content and cell morphology.Clinical significance: Under the conditions investigated, exogenous treatment of equine tendon fibroblasts with PGE2 failed to alter cell metabolism in a manner useful as a model of tendon injury. A model that applies cyclic strain to a three dimensional construct seeded with tendon fibroblasts may prove to be a more useful model and merits further investigation for this purpose. The ability to assess cellular responses in an environment where the cells are supported within the extracellular matrix may prove beneficial.
Keywords: Tendon; horse; prostaglandin; fibroblast